The exact gossiping problem for K>8 messages - Ceballo, Shaira Kim I. (2011)
This study of the exact gossiping problem extended the results for k  ≥ 8 messages. In generating the minimum number of call sequence, a step by step process was created to generate E(n,k), the minimum number of call sequence where n is the number of vertices and k the number of messages, which consequently produced the initial function. Three Lemmas were presented and were proven. These lemmas were used to prove the theorem for the exact gossiping problem k  ≥ 8 messages. The resulting function used in the problem is given
This study of the exact gossiping problem extended the results for k  ≥ 8 messages. In generating the minimum number of call sequence, a step by step process was created to generate E(n,k), the minimum number of call sequence where n is the number of vertices and k the number of messages, which consequently produced the initial function. Three Lemmas were presented and were proven. These lemmas were used to prove the theorem for the exact gossiping problem k  ≥ 8 messages. The resulting function used in the problem is given.
Keywords: Graph theory; Exact gossiping problem; Networking; k>8 messages; Lemmas; Communication